2015
DOI: 10.1186/s12889-015-1880-5
|View full text |Cite
|
Sign up to set email alerts
|

Balancing expectations amidst limitations: the dynamics of food decision-making in rural Kerala

Abstract: BackgroundFood decision-making is a complex process and varies according to the setting, based on cultural and contextual factors. The study aimed to understand the process of food decision-making in households in rural Kerala, India, to inform the design of a dietary behaviour change intervention.MethodsThree focus group discussions (FGDs) and 17 individual interviews were conducted from September 2010 to January 2011 among 13 men and 40 women, between 23 and 75 years of age. An interview guide facilitated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 34 publications
3
45
1
Order By: Relevance
“…Within the Kerala context, this phase revealed the importance of a collectivist approach to behavior change techniques with decision-making at the family level. The need for such an approach has been further supported by more in-depth studies on health behaviors, particularly dietary behavior change in relation to NCDs in this population [64]. The paucity of evidence on community-based life style interventions in India made it imperative to define context-specific objectives and strategies for personal and environmental change.…”
Section: Discussionmentioning
confidence: 99%
“…Within the Kerala context, this phase revealed the importance of a collectivist approach to behavior change techniques with decision-making at the family level. The need for such an approach has been further supported by more in-depth studies on health behaviors, particularly dietary behavior change in relation to NCDs in this population [64]. The paucity of evidence on community-based life style interventions in India made it imperative to define context-specific objectives and strategies for personal and environmental change.…”
Section: Discussionmentioning
confidence: 99%
“…It therefore becomes a challenge regarding food choices and behaviour change, as decision-making is partly influenced by all individuals in the family by virtue of various power relations, and also by society [12]. In the context of rural Kerala in India, we have already found that dietary decisions are taken at the household level and that costs were the primary consideration, money costs in particular [13, 14]. The hierarchy of household members in terms of food preferences and the value ascribed to various foodstuffs were more important than their perceived health value [13].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of rural Kerala in India, we have already found that dietary decisions are taken at the household level and that costs were the primary consideration, money costs in particular [13, 14]. The hierarchy of household members in terms of food preferences and the value ascribed to various foodstuffs were more important than their perceived health value [13]. Irrespective of their employment status, women’s identities, also strongly embedded as housewives and mothers had the primary responsibility to keep “husbands and children well fed” [15] (p. 266).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Irrespective of whether from urban or rural area people have their own beliefs and practices. 8 The roots of these kinds of customs and taboos are rational at times and some real origins cannot be traced. 9 Malnutrition is one of the most important risk factors for poor health, both directly and in directly.…”
Section: Introductionmentioning
confidence: 99%